Tracing the Political Conflict of Kyai: Analyzing the Conflictual Relation among Local Kyai in Bondowoso, East Java - Bahar, Moh. Syaeful (Indonesian Journal of Political Studies, 2024)
This study traces the trajectory of political conflict among local kiai in Bondowoso as a significant phenomenon within the dynamics of religious authority–based local politics. The research background departs from the increasing involvement of kiai in practical politics, which has triggered social fragmentation at the pesantren community level. Academically, this study highlights that religious authority is not singular in nature but is negotiated through patronage relations, pesantren networks, and political party affiliations. The research employs a qualitative approach using field study methods through observation and in-depth interviews with kiai and their followers. The findings show that political conflict among kiai is driven by differences in party preferences, pesantren alma mater backgrounds, patronage toward respected kiai figures, and political kinship ties. These conflicts emerge in latent or manifest forms, both internal and inter-party, and generate mass responses divided between emotional and rational patterns. This study confirms that political conflict among kiai reflects not only a contestation of power but also a process of redefining religious authority within Indonesian local politics.